PSO based optimization of worst-case execution time for ASIP application - Venkanna, Mood; Rao, Rameshwar; Chandra Sekhar, P (International Journal of Engineering and Technology, 2018)
Industrial requires hard real-time systems for safety and critical applications like automotive, Aeronautics, manufacturing control and train industries. Hard Real-Time Systemsâ€™ embedded controllers are with expectation of complete the tasks within a certain time bounds reliably including task scheduling. The estimation of upper bound limits corresponding to the execution times is often termed as the Worst-Case Execution Times (WCETs). It is an essential step in developing and validating the hard real-time systems. Particularly, the upper bounds need to satisfy these constraints related to the execution times. However, it is often not feasible many times to set upper bounds on execution times for programs. In present work, the problem of choosing reconfigurable Custom Instructions (CIs) is accomplished by optimizing the WCET corresponding to an application. This issue is designed using Particle Swarm Optimization (PSO) based program for a path analysis. The work emphasizes on the effectiveness of optimizing the WCET when applied to a reconfigurable processor. It evaluates a compound application of multimedia with a host of reconfigurable CIs corresponding to a number of hardware parameters.Â Â